Diels–Alder Reactions of 1,3-Dienes Incorporated into 8-Oxa- and 8-Thiabicyclo[3.2.1]octane Skeletons: A Convenient Access to Complex Tri- and Tetracyclic Compounds - Högermeier, Jens; Trawny, Daniel; Zimmer, Reinhold; Reissig, Hans-Ulrich (Synthesis, 2015)
The Diels–Alder reactions of eight different 1,3-dienes incorporated into an 8-oxa- or 8-thiabicyclo[3.2.1]octane backbone were studied employing N-phenylmaleimide as standard dienophile. The facial diastereoselectivity was very high, in all cases furnishing only products resulting from a top-face attack. The [4+2] cycloadditions proceeded often with high exo/endo selectivity depending on the substitution degree of the 1,3-diene system. For one of the 1,3-dienes it could be demonstrated that the scope of the Diels–Alder reaction is fairly broad. The approach described here allows an efficient and fast access to complex tri- and tetracyclic compounds ready for further functionalization.
Keywords: 1,3-dienes; 8-oxabicyclo[3.2.1]octanes; cycloadditions; 1H-pyrrole-2,5-diones; stereoselectivity; regioselectivity